2020
DOI: 10.1101/2020.11.08.371179
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Augmenting Flexibility: Mutual Inhibition Between Inhibitory Neurons Expands Functional Diversity

Abstract: One of the most intriguing observations of recurrent neural circuits is their flexibility. Seemingly, this flexibility extends far beyond the ability to learn, but includes the ability to use learned procedures to respond to novel situations. Here, we report that this flexibility arises from the synergistic interplay between recurrent mutual excitation and recurrent mutual inhibition. Specifically, we show that mutual inhibition is critical in expanding the functionality of the circuit, far beyond what feedbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 77 publications
(262 reference statements)
1
4
0
Order By: Relevance
“…Finally, we showed that the flexible gate switching can be used to create a 4-bit ripple carry adder. This is in line with previous research that has shown that recurrent neural networks are more flexible than their feedforward counterparts [38]. Specifically, this study takes advantage of a nearby cusp bifurcation [37].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Finally, we showed that the flexible gate switching can be used to create a 4-bit ripple carry adder. This is in line with previous research that has shown that recurrent neural networks are more flexible than their feedforward counterparts [38]. Specifically, this study takes advantage of a nearby cusp bifurcation [37].…”
Section: Discussionsupporting
confidence: 87%
“…To examine flexibility in small neural networks, we start with a CRIREL microcircuit [Fig 1a] [38]. This microcircuit is simultaneously near two cusp bifurcations [Fig 1b], and as such is capable of a simple two “bit” version of working memory [Fig 1b-c].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations